Source- and Site-Specific Earthquake Ground Motions: Application of a State-of-the-Art Evaluation Method - Nagao, T.; Fukushima, Y. (Engineering, Technology & Applied Science Research, 2020)
Seismic design is the preparation for earthquake ground motions considering the seismicity and seismic amplification properties of the ground at the target site. However, the effects of source, path, and site amplification characteristics are not sufficiently anticipated in seismic codes. Regarding the source and path characteristics, earthquakes that have the strongest influence on the target site should be considered specifically, and, concerning seismic amplification, the effects of not only a shallow subsurface but also a deep subsurface should be considered. This article takes the design spectra of Japanese highway bridges as an object and compares them with the spectra produced by a ground motion prediction equation and the source- and site-specific spectra evaluated using a state-of-the-art method. The results show that the spectra differ greatly. In this way, the necessity of the application of a state-of-the-art technique in the evaluation of source, path, and site amplification characteristics is demonstrated.